Analisis Konten Buku Cerita “Aku Sayang Tubuhku” sebagai Media Pendidikan Seksual untuk Anak Usia Dini - Susana Kamilah Susan (Jambura Early Childhood Education Journal, 2021)
This study aims to find out how the content of the book "I Love My Body" becomes a medium that is in accordance with the development of early childhood and appropriate or not the content of the book "I Love My Body" as a medium of sexual education for early childhood. This research uses qualitative method, Content Analysis research design, using text study and research instrument. The results of this study obtained that the storybook I Love My Body in accordance with 5 out of 6 indicators of aspects of child development, namely in the arts, cognitive, language, religious morals, and socio-emotional, while in motor development this book is less able to support the development of children. In the indicators of conformity with sexual education for early childhood was found in accordance with the eight indicators that have been formulated, namely introducing body parts and functions, instilling shame, providing understanding of toilet training and caring for their genital organs, understanding gender, instilling the soul of masculinity and femininity, preventing children from acts of violence, understanding the parts of the body that can and should not be touched, and understanding appropriate and inappropriate touching. Keyword: sexual education, learning media, storybooks, early childhood, content analysis Penelitian ini bertujuan mengetahui besar pengaruh buku cerita “Aku Sayang Tubuhku” dalam mengembangkan aspek perkembangan dan pendidikan seksual anak usia dini. Penelitian ini menggunakan metode kualitatif, desain Content Analysis, menggunakan penelaahan teks dan instrumen penelitian. Hasil penelitian ini diperoleh bahwa buku cerita Aku Sayang Tubuhku sesuai dengan 5 dari 6 indikator aspek perkembangan anak, yaitu dalam seni, kognitif, bahasa, moral agama, dan sosio emosional, sedangkan dalam perkembangan motorik buku ini kurang dapat menstimulus perkembangan anak. Dalam indikator kesesuaian dengan pendidikan seksual untuk anak usia dini ditemukan sesuai 7 dari 8 indikator yang telah dirumuskan yaitu mengenalkan bagian tubuh dan fungsinya, menanamkan rasa malu, kurang memberikan pemahaman toilet training dan merawat organ genitalnya, pemahaman gender, menanamkan jiwa maskulinitas dan feminitas, mencegah anak dari tindakan kekerasan, memahami bagian tubuh yang boleh dan tidak boleh disentuh, serta memahami sentuhan yang pantas dan tidak pantas. Kata kunci: Pendidikan Seksual, Media Pembelajaran, Buku Cerita, Anak Usia Dini, Analisis Konten